Crural tissues histopathology and clinical-morphological correlations in patients with traumatic osteomyelitis, combined with trophic disorders - Hryhorovskyi, Valeriy; Hrytsai, Mykola; Tsokalo, Vasyl; Kolov, Hennadiy; Hrygorovska, Anastasiia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Detailed analytical study of pathologic changes that would display features of the damaged tissues condition at the traumatic osteomyelitis (TO) combined with trophic disorders are important for treatment tactics. Objective: to determine the frequency and correlations between clinical and morphometric parameters on the basis of the graded morphometric analysis of changes that occur in the injured tissues in patients with tibia TO and crural tissues with trophic disorders. Methods: fragments of the damaged crural tissues (bone, soft tissues, skin) from 38 patients with TO were studied. We used: clinical examination and determined the degree of trophic disorders; visualising methods, histologic research with morphometric parameters estimations, the analysis of correlations between clinical and morphometric parameters. Results: trophic disorders in extremity tissues (bone, soft tissues, muscles, skin) which were observed at TO, represented a complex of pathological changes: ischemic, necrotic, dystrophic, atrophic, inflammatory, reparative which combined in various proportions. The closest correlations of morphometric parameters were found with such clinical indicators as «gender», «type of fracture» and «term of the latest debridement». Conclusions: аt TO of the tibia, combined with trophic disorders, some correlations between clinical and morphometric parameters of involved extremity tissues were found. The revealed dependences are important for evaluation of tissue damage grade by known clinical indicators values that should promote predicting of disease course and its consequences, planning of medical interventions.